A new energy soft-pack battery aluminum-plastic film self-assembly CPP base film and preparation method thereof

By introducing organic micro-nano thermal conduction materials into the aluminum-plastic film of new energy soft-pack battery, the CPP heat seal layer is induced to self-assemble, which solves the problem of difficult battery gas discharge under high temperature conditions and realizes the safety and stability of the battery at high temperatures.

CN119099190BActive Publication Date: 2025-04-18GUIZHOU INST OF METALLURGY & CHEM ENG +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411234844.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-04-18
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively discharge gas inside the battery under high temperature conditions, resulting in a short circuit or an increase in pressure to cause an explosion, which poses serious safety hazards.

Method used

The CPP base film is self-assembled by a new energy soft-pack battery aluminum-plastic film. By introducing organic micro-nano thermal conduction materials into the CPP base film, the CPP heat seal layer is induced to produce a self-assembly function, thereby automatically reducing the heat seal strength under high temperature conditions, releasing gas, and preventing the battery from exploded.

Benefits of technology

It realizes the automatic removal of gases generated by the increase in the temperature of the battery electrolyte under high temperature conditions, prevents explosions caused by the increase in the internal pressure of the battery, and effectively prevents safety hazards of soft-pack batteries in new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119099190B_ABST
    Figure CN119099190B_ABST
Patent Text Reader

Abstract

The present invention discloses a self-assembled CPP base film of aluminum-plastic film of new energy soft-pack battery and a preparation method thereof. The self-assembled CPP base film of aluminum-plastic film of new energy soft-pack battery comprises a self-assembled heat-sealing layer, a supporting layer and a composite layer arranged in sequence; the thickness of the CPP base film is 20 μm to 90 μm, and the thickness ratio of the self-assembled heat-sealing layer, the supporting layer and the composite layer is (1-3):(4-8):(1-3). In the preparation process, the raw materials of the heat-sealing layer, the supporting layer and the composite layer are put into the extruder corresponding to the three-layer co-extrusion casting machine, and after setting the three-layer thickness ratio and the extruder processing temperature, the film is prepared by the co-extrusion casting process, and then the corona machine is used for corona treatment to obtain the self-assembled CPP base film of aluminum-plastic film of new energy soft-pack battery. The present invention uses organic hybrid micro-nano heat conductive materials to induce the CPP film heat-sealing layer to produce a self-assembly function in a high temperature environment after heat sealing, which effectively prevents the soft-pack battery from short-circuiting or exploding in a high temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery packaging materials, and more specifically to a new energy soft-pack battery aluminum-plastic film self-assembled CPP base film and a preparation method thereof. Background Art

[0002] The aluminum-plastic film for lithium-ion battery soft packaging is a composite soft packaging material composed of a substrate (such as BOPA), aluminum foil, a sealing layer (such as CPP) and an adhesive. As a packaging material for lithium batteries, the aluminum-plastic film must have good heat sealing performance, insulation, mechanical strength and ductility. It must also have a barrier to moisture and oxygen, as well as very high chemical stability to corrosive acids, alkalis, salts, etc. inside the battery. As the inner layer of the aluminum-plastic film, the fundamental core requirement of CPP is to play a sealing and insulating role. The damage of soft-packaged batteries mainly occurs at the sealing part of the battery, so the heat sealing strength of the sealing position during long-term use or storage is a very critical parameter. Under normal temperature conditions, the battery sealing part is required to have a high heat sealing strength to ensure the long-term safe use of the battery. However, in high temperature scenarios, the heat sealing strength of the sealing part of the soft-pack battery is too high, and the electrolyte inside the battery is prone to produce a large amount of gas in a high temperature environment and cannot be discharged in time, which will cause a short circuit inside the battery or high pressure to cause the battery to explode, causing serious safety hazards. Especially for power batteries, in high-rate and high-heat generation scenarios, the gas inside the battery above 120°C needs to be discharged in time to prevent battery explosion and safety accidents.

[0003] At present, there has been no relevant technical breakthrough in the problem of timely discharge of high-temperature gas in soft-pack batteries, and there are few reports at home and abroad. Therefore, how to provide a new technology is an urgent problem to be solved by technical personnel in this field. Summary of the invention

[0004] In view of this, the present invention innovatively provides a new energy soft-pack battery aluminum-plastic film self-assembled CPP base film and a preparation method thereof, and utilizes organic micro-nano thermal conductive materials to induce the CPP heat sealing layer to produce self-assembly function to better solve the above problems.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A self-assembled CPP base film of aluminum-plastic film for new energy soft-pack batteries, comprising a self-assembled heat-sealing layer, a support layer and a composite layer arranged in sequence; the thickness of the CPP base film is 20 μm to 90 μm, and the thickness ratio of the self-assembled heat-sealing layer, the support layer and the composite layer is (1-3): (4-8): (1-3).

[0007] Preferably, the self-assembled heat-sealing layer comprises, by weight percentage, 69% to 96% of ternary random copolymer polypropylene, 0% to 20% of binary random copolymer polypropylene, 3% to 6% of opening lubricant and 1% to 5% of organic hybrid micro-nano heat conductive material.

[0008] Furthermore, the opening lubricant is one or more of organic silicones, siloxane polymers, and high molecular weight silicone waxes; the organic hybrid micro-nano thermal conductive material is an organic hybrid micro-nano thermal conductive material prepared by a sol-gel method using one or more organic surface modifiers such as silicon dioxide, calcium carbonate, calcium silicate, and barium sulfate.

[0009] Furthermore, the preparation method of the organic hybrid micro-nano thermal conductive material is:

[0010] The organic surface modifier and the inorganic nanomaterial are mixed in a mass ratio of 1:99 to 5:95, and then prepared by a sol-gel method, with a temperature of -10 to 120°C, a pressure of 1.0 MPa to 3.0 MPa, and a reaction time of 1 h to 10 h.

[0011] The organic surface modifier is one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, and a borate coupling agent.

[0012] Preferably, the support layer comprises, by weight percentage, 50% to 90% block copolymer polypropylene, 0% to 10% binary random copolymer polypropylene, 0% to 10% ternary random copolymer polypropylene, 5% to 10% polyolefin elastomer, and 5% to 20% acidified polypropylene.

[0013] Furthermore, the polyolefin elastomer is one or more of polypropylene elastomer, polyethylene elastomer, ethylene propylene rubber, and ultra-low density polyethylene; the selected block polypropylene has a melting point of ≥163°C and a melt index of 2-10g / 10min, preferably 3-8g / 10min.

[0014] Furthermore, the ternary random copolymer polypropylene has a melting point of 125°C to 135°C, a melt index of 3 to 12 g / 10 min (230°C, 2.16 kg), and a melt index of preferably 5 to 9 g / 10 min.

[0015] Preferably, the composite layer comprises, by weight percentage, 50% to 89% binary random copolymer polypropylene, 5% to 15% block copolymer polypropylene, 5% to 30% acidified polypropylene, and 1% to 5% vinyl acetate.

[0016] Furthermore, the acidified polypropylene is maleic anhydride grafted modified polypropylene, with a grafting rate of ≥2% and a melt index of 3-12 g / 10 min.

[0017] Furthermore, the binary random copolymer polypropylene has a melting point of ≥140°C and a melt index of 3-12 g / 10 min, preferably 5-9 g / 10 min.

[0018] Preferably, the acetic acid content of the vinyl acetate is 20wt%~30wt%, and the melt index is 10~30g / 10min.

[0019] In addition, the present invention also provides a method for preparing a CPP base film for self-assembly of an aluminum-plastic film for a new energy soft-pack battery as described in the above technical solution, comprising the following steps:

[0020] (1) Weigh the raw materials of the self-assembly heat-sealing layer, the support layer and the composite layer according to weight percentage;

[0021] (2) The raw materials of the self-assembled heat-sealing layer, the support layer and the composite layer are respectively put into the corresponding A, B and C extruders of the three-layer co-extrusion casting machine, and the equipment is started after being adjusted according to the layer thickness ratio and the extruder processing temperature. The film is prepared by the co-extrusion casting process, and then a corona machine is used for corona treatment with an output power of 2~70KW and an output frequency of 10~25kHz to obtain the self-assembled CPP base film of the aluminum-plastic film of the new energy soft-pack battery.

[0022] Preferably, in step (2), the extrusion temperature of extruders A and C is 230°C, and the extrusion temperature of extruder B is 255°C.

[0023] It can be seen from the above technical solution that, compared with the prior art, the present invention discloses a new energy soft-pack battery aluminum-plastic film self-assembled CPP base film and a preparation method thereof, which has the following beneficial effects:

[0024] The aluminum-plastic film self-assembled CPP base film prepared by the present invention is prepared by a three-layer co-extrusion process, and is composed of a first self-assembled heat-sealing layer (inner layer), a second support layer (core layer) and a third composite layer (surface layer). The self-assembled CPP film prepared by adjusting the proportion of each layer shows good heat-sealing strength after heat-sealing cooling, and has good bonding strength between functional layers. Under high temperature (>120°C), the heat-sealing bonding is induced by organic hybrid micro-nano heat-conducting materials, and polypropylene undergoes a phase transition to a viscous flow state, and the heat-sealing strength decreases and automatically presents more micropores. When the temperature decreases, the heat-sealing strength increases and the micropores are automatically closed, showing good self-assembly function, while taking into account good electrolyte resistance and no stress whitening phenomenon. When used in soft-pack batteries for new energy vehicles, the gas generated by the increase in the temperature of the electrolyte inside the battery will be automatically removed under high temperature conditions, preventing the bulging explosion caused by the increase in the internal pressure of the battery, and effectively preventing the safety hazards of soft-pack batteries for new energy vehicles. The production method provided by the present invention is produced by a three-layer co-extrusion casting process, which is simple to manufacture, low in cost, rich in raw material sources and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0026] Figure 1 It is a schematic diagram of the production process of the aluminum-plastic film self-assembled CPP base film of the present invention. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] In terms of weight percentage, the self-assembled heat sealing layer is prepared by using 90% ternary random copolymer polypropylene, 5% binary random copolymer polypropylene, 3% opening lubricant and 2% organic hybrid micro-nano thermal conductive material, wherein the ternary random copolymer polypropylene has a melting point of 131°C and a melt index of 7.6g / 10min; the binary random copolymer polypropylene (Shanghai Petrochemical 800E) has a melting point of 143°C and a melt index of 7.5g / 10min; the organic hybrid micro-nano thermal conductive material is a self-made monodisperse organic hybrid silica thermal conductive material, and the specific preparation method is as follows:

[0030] Silane coupling agent and nano-silicon dioxide were mixed in a mass ratio of 3:97, and the sol-gel method was used with a temperature of 850°C, a pressure of 2.0 MPa, and a reaction time of 7 h.

[0031] The support layer is prepared by using 70% block copolymer polypropylene, 5% binary random copolymer polypropylene (Shanghai Petrochemical 800E), 5% ternary random copolymer polypropylene (Maoming Petrochemical F4908), 8% polyolefin elastomer and 12% acidified polypropylene, wherein the block copolymer polypropylene (Maoming Petrochemical HR2106M) has a melting point of 165°C and a melt index of 5.2g / 10min; polyolefin elastomer (Vistamax 6202); acidified polypropylene resin (Guangzhou Lushan AP302N);

[0032] The composite layer was prepared by using 80% binary random copolymer polypropylene (Shanghai Petrochemical 800E), 5% block copolymer polypropylene (Maoming Petrochemical HR2106M), 12% acidified polypropylene (Guangzhou Lushan AP302N) and 3% vinyl acetate (Zhongkelai Refining UE2825).

[0033] The raw materials of the heat sealing layer, the supporting layer and the composite layer are mixed according to weight percentage, and put into the extruder corresponding to the three-layer co-extrusion casting machine (the layer structure is ABC), the thickness ratio of the three layers is set to 1:8:1, the temperature of the B extruder is set to 255°C, and the temperatures of the A and C extruders are set to 230°C. An 80um self-assembled CPP film is made through a co-extrusion casting process, and a corona machine is used for corona treatment with an output power of 2~70KW and an output frequency of 10~25kHz. The surface tension of the composite layer under the machine is ≥42dyn.

[0034] Example 2

[0035] In terms of weight percentage, the self-assembled heat sealing layer is prepared by using 85% ternary random copolymer polypropylene, 8% binary random copolymer polypropylene, 4% opening lubricant and 3% organic hybrid micro-nano thermal conductive material, wherein the ternary random copolymer polypropylene has a melting point of 131°C and a melt index of 7.6g / 10min; the binary random copolymer polypropylene (Shanghai Petrochemical 800E) has a melting point of 143°C and a melt index of 7.5g / 10min; the organic hybrid micro-nano thermal conductive material is a self-made monodisperse organic hybrid silica thermal conductive material, and the specific preparation method is as follows:

[0036] Silane coupling agent and nano-silicon dioxide were mixed in a mass ratio of 3:97, and the sol-gel method was used with a temperature of 850°C, a pressure of 2.0 MPa, and a reaction time of 7 h.

[0037] The support layer is prepared by using 72% block copolymer polypropylene, 7% binary random copolymer polypropylene (Shanghai Petrochemical 800E), 3% ternary random copolymer polypropylene (Maoming Petrochemical F4908), 8% polyolefin elastomer and 10% acidified polypropylene, wherein the block copolymer polypropylene (Maoming Petrochemical HR2106M) has a melting point of 165°C and a melt index of 5.2g / 10min; polyolefin elastomer (Vistamax 6202); acidified polypropylene resin (Guangzhou Lushan AP302N);

[0038] The composite layer was prepared by using 75% binary random copolymer polypropylene (Shanghai Petrochemical 800E), 7% block copolymer polypropylene (Maoming Petrochemical HR2106M), 15% acidified polypropylene (Guangzhou Lushan AP302N) and 3% vinyl acetate (Zhongkelai Refining UE2825).

[0039] The raw materials of the heat sealing layer, the supporting layer and the composite layer are mixed respectively according to the weight percentage, and put into the extruder corresponding to the three-layer co-extrusion casting machine (the layer structure is ABC), the thickness ratio of the three layers is set to 2:6:2, the temperature of the B extruder is set to 255°C, and the temperatures of the A and C extruders are set to 230°C. An 80um self-assembled CPP film is made through a co-extrusion casting process, and a corona machine is used for corona treatment with an output power of 2~70KW and an output frequency of 10~25kHz. The surface tension of the composite layer under the machine is ≥42dyn.

[0040] Example 3

[0041] In terms of weight percentage, 94% ternary random copolymer polypropylene, 5% opening lubricant and 1% organic hybrid micro-nano thermal conductive material are used to prepare the self-assembled heat sealing layer, wherein the ternary random copolymer polypropylene has a melting point of 131°C and a melt index of 7.6g / 10min; the binary random copolymer polypropylene (Shanghai Petrochemical 800E) has a melting point of 143°C and a melt index of 7.5g / 10min; the organic hybrid micro-nano thermal conductive material is a self-made monodisperse organic hybrid silica thermal conductive material, and the specific preparation method is as follows:

[0042] Silane coupling agent and nano-silicon dioxide were mixed in a mass ratio of 3:97, and the sol-gel method was used with a temperature of 850°C, a pressure of 2.0 MPa, and a reaction time of 7 h.

[0043] The support layer is prepared by using 75% block copolymer polypropylene, 5% ternary random copolymer polypropylene (Maoming Petrochemical F4908), 10% polyolefin elastomer and 10% acidified polypropylene, wherein the block copolymer polypropylene (Maoming Petrochemical HR2106M) has a melting point of 165°C and a melt index of 5.2g / 10min; polyolefin elastomer (Vistamax 6202); acidified polypropylene resin (Guangzhou Lushan AP302N);

[0044] The composite layer was prepared by using 65% binary random copolymer polypropylene (Shanghai Petrochemical 800E), 10% block copolymer polypropylene (Maoming Petrochemical HR2106M), 20% acidified polypropylene (Guangzhou Lushan AP302N) and 5% vinyl acetate (Zhongkelai Refining UE2825).

[0045] The raw materials of the heat sealing layer, the supporting layer and the composite layer are mixed respectively according to the weight percentage, and put into the extruder corresponding to the three-layer co-extrusion casting machine (the layer structure is ABC), the thickness ratio of the three layers is set to 1.5:7:1.5, the temperature of the B extruder is set to 255°C, and the temperatures of the A and C extruders are set to 230°C. An 80um self-assembled CPP film is made through a co-extrusion casting process, and a corona machine is used for corona treatment with an output power of 2~70KW and an output frequency of 10~25kHz. The surface tension of the composite layer under the machine is ≥42dyn.

[0046] Comparative Example 1

[0047] This comparative example uses Xinlun New Materials aluminum-plastic film H152-EL.

[0048] Comparative Example 2

[0049] This comparative example uses Mingguan New Materials aluminum-plastic film CAP153.

[0050] Comparative Example 3

[0051] This comparative example uses Daoming Optical Aluminum-Plastic Film DM-L152N.

[0052] Performance Testing

[0053] The CPP films in the above Examples 1 to 3 and Comparative Examples 1 to 3 were made into aluminum-plastic films (aluminum foil layer thickness 40 um, nylon layer thickness 25 um), and after the aluminum-plastic films were heat-sealed, low-temperature heat-seal strength tests and high-temperature heat-seal strength tests, thermal peel strength evaluations, and deep-drawing performance tests were performed.

[0054] The test method is as follows:

[0055] 1. Heat seal strength test: Heat seal the aluminum-plastic film according to TCIAPS0005-2018 standard, and set the test environment temperature to room temperature 23℃ and high temperature 130℃;

[0056] 2. Thermal peel strength test: The composite aluminum-plastic film samples are immersed in 120℃ electrolyte for 24 hours (in a closed container). After taking out the samples, a tensile tester is used to quickly test the composite peel strength of the CPP and aluminum foil layer.

[0057] 3. Deep punching performance test: Use a deep punching tester to test the deep punching performance of aluminum plastic film and evaluate the deep punching resistance of CPP film. The punching depth is 8mm, and the stress whitening and cracking are observed. Five groups of samples are tested each time. The test results are shown in the following table:

[0058]

[0059] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0060] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A self-assembled CPP base film for aluminum-plastic film of new energy soft-pack battery, characterized in that: It comprises a self-assembled heat-sealing layer, a supporting layer and a composite layer arranged in sequence; the thickness of the CPP base film is 20 μm to 90 μm, and the thickness ratio of the self-assembled heat-sealing layer, the supporting layer and the composite layer is (1-3): (4-8): (1-3); The self-assembled heat-sealing layer comprises, by weight percentage, 69% to 96% of ternary random copolymer polypropylene, 0% to 20% of binary random copolymer polypropylene, 3% to 6% of opening lubricant, and 1% to 5% of organic hybrid micro-nano heat conductive material; The organic hybrid micro-nano heat conductive material is an organic hybrid micro-nano heat conductive material prepared by a sol-gel method using one or more organic surface modifiers such as silicon dioxide, calcium carbonate, calcium silicate, and barium sulfate. The preparation method of the organic hybrid micro-nano heat conductive material is as follows: The organic surface modifier and the inorganic nanomaterial are mixed in a mass ratio of 1:99 to 5:95, and prepared by a sol-gel method, with the temperature controlled at -10 to 120°C, the pressure at 1.0 MPa to 3.0 MPa, and the reaction time at 1 h to 10 h; wherein the organic surface modifier is one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, and a borate coupling agent; The support layer comprises, by weight percentage, 50% to 90% of block copolymer polypropylene, 0% to 10% of binary random copolymer polypropylene, 0% to 10% of ternary random copolymer polypropylene, 5% to 10% of polyolefin elastomer, and 5% to 20% of acidified polypropylene; The composite layer comprises, by weight percentage, 50% to 89% binary random copolymer polypropylene, 5% to 15% block copolymer polypropylene, 5% to 30% acidified polypropylene, and 1% to 5% vinyl acetate; The acidified polypropylene is maleic anhydride grafted modified polypropylene, with a grafting rate of ≥2% and a melt index of 3-12 g / 10 min.

2. The aluminum-plastic film self-assembly CPP base film for new energy soft-pack batteries according to claim 1, characterized in that: The opening lubricant is one or more of organic silicones, siloxane polymers, and high molecular weight silicone waxes.

3. The aluminum-plastic film self-assembled CPP base film for new energy soft-pack batteries according to claim 1, characterized in that: The polyolefin elastomer is one or more of polypropylene elastomer, polyethylene elastomer, ethylene propylene rubber, and ultra-low density polyethylene; the selected block polypropylene has a melting point of ≥163°C and a melt index of 2-10g / 10min.

4. The aluminum-plastic film self-assembly CPP base film for new energy soft-pack batteries according to claim 1, characterized in that: The ternary random copolymer polypropylene has a melting point of 125° C. to 135° C. and a melt index of 3 to 12 g / 10 min.

5. The aluminum-plastic film self-assembly CPP base film for new energy soft-pack batteries according to claim 1, characterized in that: The binary random copolymer polypropylene has a melting point of ≥140° C. and a melt index of 3-12 g / 10 min.

6. The aluminum-plastic film self-assembly CPP base film for new energy soft-pack batteries according to claim 1, characterized in that: The vinyl acetate has an acetic acid content of 20 wt% to 30 wt% and a melt index of 10 to 30 g / 10 min.

7. A method for preparing a CPP-based film for self-assembly of aluminum-plastic films for new energy soft-pack batteries according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Weigh the raw materials of the self-assembly heat-sealing layer, the support layer and the composite layer according to weight percentage; (2) The raw materials of the self-assembled heat sealing layer, the support layer and the composite layer are respectively put into the corresponding A, B and C extruders of the three-layer co-extrusion casting machine, and the equipment is adjusted according to the layer thickness ratio and the extruder processing temperature and then started to prepare the film by the co-extrusion casting process. Then, a corona machine is used for corona treatment with an output power of 2-70 kW and an output frequency of 10-25 kHz to obtain the self-assembled CPP base film of the aluminum-plastic film for new energy soft-pack batteries.

8. The method for preparing a CPP base film for self-assembly of aluminum-plastic film for new energy soft-pack battery according to claim 7, characterized in that: In step (2), the extrusion temperature of extruders A and C is 230°C, and the extrusion temperature of extruder B is 255°C.

Citation Information

Patent Citations

  • High strength exhaust sealing layer and lithium ion battery flexible packaging material based on same

    CN106042566A

  • Novel safe aluminum-plastic film

    CN114074461A